Personal protective equipment training & lived experience for healthcare staff during COVID-19. (April 2022) - Cahill, J.; Kay, A.; Howard, V.; Mulcahy, B.; Forde, M.; George, S.; Ziampra, E.; Duffy, F.; Lacey, G.; Fitzpatrick, F.
Highlights: Staff experience (n = 45) during COVID-19 & personal protective equipment (PPE) use was described. COVID-19 has impacted staff social life/home-work interface (80%) and mental health (42%). Knowledge of procedures was the most cited risk associated with PPE use (40%). Contributory factors to PPE errors included inadequate time (43%) and staffing pressures (29%). The majority (78%) supported mindfulness integration into PPE practice. Abstract: Objectives: To describe the lived experience of healthcare staff during the Coronavirus Disease 2019 (COVID-19) pandemic relating to the use of personal protective equipment (PPE) and investigate risks associated with PPE use, error mitigation and acceptability of mindfulness incorporation into PPE practice. Methods: A qualitative human factors' study at two Irish hospitals occurred in late 2020. Data was collected by semi-structured interview and included role description, pre-COVID-19 PPE experience, the impact of COVID-19 on lived experience, risks associated with PPE use, contributory factors to errors, error mitigation strategies and acceptability of incorporating mindfulness into PPE practice. Results: Of 45 participants, 23 of whom were nursing staff (51%), 34 (76%) had previously worn PPE and 25 (56%) used a buddy system. COVID-19 lived experience impacted most on social life/home-work interface (n = 36, 80%). Nineteen staff (42%) described mental health impacts. The most cited risk concerned 'knowledge of procedures' (n = 18, 40%). Contributory factors to PPE errors included time (n = 15, 43%) and staffing pressures (n = 10, 29%). Mitigation interventions included training/education (n = 12, 40%). The majority (n = 35, 78%) supported mindfulness integration into PPE practice. Conclusions: PPE training should address healthcare staff lived experiences and consider incorporation of mindfulness and key organisational factors contributing to safety.